Research on the rock cutting performance and feasibility verification of small-scale rotary cutting test for disc cutter - Zilong Yang; Yong Hu; Mingxu Xu; Hao Pang; Youpeng Gu; Baicheng Zheng (Scientific Reports)
Abstract Small-scale rock cutting tests serve as a simple approach to evaluate the performance of tunnel boring machines (TBMs), but the feasibility of this method requires further investigation. Herein, a small-scale rotary cutting machine is developed to conduct rock cutting tests, and the cutting performance is investigated. The results indicate that similar cutting performance can be achieved through both small-scale and full-scale tests. The critical penetration depth for effective rock cutting by the cutter is 0.5 mm, below which the cutter grinds against the rock. The optimal ratio of cutting spacing to penetration depth obtained in small-scale tests is 4.47. A result within the empirical range can be achieved by multiplying the optimal small-scale cutting parameters with the scale coefficient, demonstrating the feasibility of using small-scale tests to guide the design of cutter heads. Based on the test result, the scale prediction model is constructed to predict the full-scale cutting force. The predictive capability of the proposed model and CSM model is validated using 72 sets of full-scale test data involving the same types of rock, and the predictions of the proposed model are closer to the test data.